PERAN PPI - KOREA PERPIKA DALAM PENGEMBANGAN POTENSI PRODUKTIVITAS SUMBER DAYA MANUSIA INDONESIA MELALUI YOUTH DIPLOMACY (2017-2020) - Annisa Setiani Hidayat, (2022)
The increasing number of youth demography have been the concern of Indonesian government these past few years or in the future, and youth diplomacy have become the popular solution to approach this problem. Within the period of 2017 - 2020, this research aims to enhance the role of youth community especially student exchange community. Hereby, the focus on this research is how youth community (PERPIKA) could take part in the development of their human resources through their work program. The method that is used in this research is qualitative descriptive, so that this research could help to describe the process in details and as real as possible. The data is collected through observation through internship at Ministry of Foreign Affair of Indonesia, interview one of the members at PERPIKA and MoFA staff, and to complement the data, research through official document, report, online platform etc. is included. This Research discusses on how youth community such as Indonesian Student Exchange (PPI) in South Korea (PERPIKA) fulfil their role at developing human resource potential and productivity through youth and public diplomacy approach. Align with their role as a diplomacy actor, PERPIKA through their internal and external work program create a whole opportunity for their member to have a positive development, that include the development of youth, labor quality and labor productivity. This research will enlighten the view on how student community as one of the IR actors and their role to achieve work requirement skills and self-development in progress. It is also proven that international student community do have a significant role at many aspects such as impact to labor productivity, labor quality and other opportunities to experience the real world of work. And it shows in IPP an APO that the outcome always increases each year and there is a significant difference of number in the database for both youngsters and older.